Penerapan Kurikulum Merdeka pada Pendidikan Anak Usia Dini di Kabupaten Jember - Sudirman, Sriwati; Jatmikowati, Tri Endang; Kusumaningtias, Nuraini (Indonesian Journal Publisher, 2023)
The curriculum is present as a guideline used by educators where the curriculum experienced various changes as a form of adaptation to a dynamic era. Wrong one of which is by implementing an independent learning curriculum where this curriculum is considered new. The purpose of this research is to identify and obtain information about the implementation of the independent learning curriculum in Jember Regency. The method used in this study is a quantitative descriptive method, which describes objects about situations and data obtained during observations so that they become useful information and are easily understood by readers. This study explains and provides an overview of the implementation of the independent learning curriculum in Jember Regency, to find out schools that have implemented the independent learning curriculum and those that have not implemented the independent learning curriculum. The results obtained were 961 kindergartens in Jember Regency, only 6 kindergartens had implemented the independent learning curriculum, while 599 had not implemented the independent learning curriculum